CONTROL OF ZOOPHILIC FLIES’ ATTACKING DAIRY COWS IN LIVESTOCK PREMISES - Shevchenko, A. M. (Scientific Progress & Innovations, 2019)
Parasitic insects are a significant problem for dairy farming in Ukraine as well as all over the world. Losses of livestock from midges in some countries can reach several million dollars. Treatment of animals with insecticides, among which the group of synthetic pyrethroids should be separately distinguished, is considered to be the most effective way to protect against midges The aim of the paper was to study insecticidalrepellent efficacy of “Ectosan-plusтм” (LLC “Brovafarma”) in different dilutions against zoophilic flies. “Ectosan-plusтм” consists of two synergistic active ingredients: alfametryn (7.5 %) and piperonil-butoxide (10.5 %), and a mixture of essential oils of lemon and rose (10 %). “Ectosan-plusтм” is a transparent oily liquid of yellowish color with a mild pleasant specific odor. The parasitological research on testing the impact of insecticide “Ectosan-plusтм” in dilutions of 1:1000 and 1:750 on flying insects was conducted on three groups of cows. At first, the increased activity of the stable fly, Stomoxys calcitrans, was established on the experimental farm under the following weather conditions: the average daytime air temperature was + 19–21 °С, the nighttime one – +8–12 °С. It was proved that the water solution (1:750) of “Ectosanplusтм” should be used once every two days for the effective protection of dairy cows against the stable flies’ attack in the farm premises. The insect repellent effectiveness (IRE) of the spray material is more than 80 %. The rate of the preparation consumption is 250 cm3 per animal. Repeated treatment of animals with the solution increases the insecticidal activity of the preparation up to three days, which indicates its probable cumulative effect. In case of a moderate or low intensity of the zoophilic flies’ attack on cows, the sufficient treatment is once every three days; in case of high intensity – every two days. The water solution of “Ectosan-plusтм” in the dilution of 1:1000 does not provide sufficient protection of cows during daylight time as the SF reduces to 69,0 % in 6 hours after the treatment. Throughout all the experiment period, no external signs of intoxication were detected in the test animals.